Wireless charging LED mediated type I photodynamic therapy of breast cancer using NIR AIE photosensitizer - Chengbin Yang; Shiqi Tang; Qiqi Liu; Miaozhuang Fan; Wenguang Zhang; Yingyu Liu; Xin Chen; Gaixia Xu; Xiaoyan Chen; Zhourui Xu (iScience)
Summary: Due to limited light penetration and dependence on oxygen, photodynamic therapy (PDT) is typically restricted to treating shallow tissues. Developing strategies to overcome these limitations and effectively using PDT for tumor treatment is a significant yet unresolved challenge. In this study, we present a smart approach combining a wireless-charged LED (wLED) with a type I aggregation-induced emission photosensitizer, MeOTTMN, to address both light penetration and tumor hypoxia issues simultaneously. MeOTTMN, characterized by twisted molecular architecture and strong intramolecular electron donor-acceptor interaction, produces high levels of hydroxyl and superoxide radicals and emits near-infrared light in its aggregated state, thus facilitating fluorescence imaging-guided PDT once formulated into nanoparticles. The inhibition of breast cancer xenografts provides compelling evidence of the treatment efficacy of type I PDT irradiated through an implantable wLED. This strategy provides a conceptual and practical paradigm to overcome key clinical limitations of PDT, expanding possibilities for clinical translation.